2020
DOI: 10.1091/mbc.e20-06-0415
|View full text |Cite
|
Sign up to set email alerts
|

NuMA interaction with chromatin is vital for proper chromosome decondensation at the mitotic exit

Abstract: NuMA is an abundant long coiled-coil protein that plays a prominent role in spindle organization during mitosis. In interphase, NuMA is localized to the nucleus and hypothesized to control gene expression and chromatin organization. However, because of the prominent mitotic phenotype upon NuMA loss, its precise function in the interphase nucleus remains elusive. Here, we report that NuMA is associated with chromatin in interphase and prophase but released upon nuclear envelope breakdown (NEBD) by the action of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…To track the spatiotemporal localization of NuMA, we performed live-cell imaging in monoclonal stable HeLa Kyoto cells coexpressing AcGFP (Aequora coerulescens GFP) and a mono FLAG epitope-tagged NuMA and mCherry-H2B (Rajeevan et al, 2020). Analogous to endogenous protein, AcGFP-NuMA localizes to the equatorial membrane in cells transfected with Ect2 siRNA, compared to control cells (Figure 1R-1T).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To track the spatiotemporal localization of NuMA, we performed live-cell imaging in monoclonal stable HeLa Kyoto cells coexpressing AcGFP (Aequora coerulescens GFP) and a mono FLAG epitope-tagged NuMA and mCherry-H2B (Rajeevan et al, 2020). Analogous to endogenous protein, AcGFP-NuMA localizes to the equatorial membrane in cells transfected with Ect2 siRNA, compared to control cells (Figure 1R-1T).…”
Section: Resultsmentioning
confidence: 99%
“…siRNA resistant Ect2 full-length and Ect2 r Δmem was cloned into a pIRES-AcGFP-FLAG plasmid (a gift from Mark Petronczki) using Age1 and EcoR1 sites. NuMA full-length was cloned into the pIRES-AcGFP-FLAG plasmid using Age1 and EcoR1 sites as reported in Rajeevan et al, 2020. All the clones were confirmed by sequencing analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, human NuMA was reported to interact with defined DNA sequences called matrix attached regions (MARs) in vitro (Luderus et al, 1994). Recently, two studies demonstrated that the C-terminal region of human NuMA interacts with DNA in vitro and chromatin in cells (Rajeevan et al, 2020;Serra-Marques et al, 2020). Rajeevan et al (2020) showed that the C-terminus NuMA 2058−2115 fragment is sufficient to bind DNA in vitro, and the basic amino acids within the region are critical for its interaction with chromatin in cells (Figure 2C).…”
Section: Dna-binding Domain In Numa's C-terminal Regionmentioning
confidence: 99%
“…Recently, two studies demonstrated that the C-terminal region of human NuMA interacts with DNA in vitro and chromatin in cells (Rajeevan et al, 2020;Serra-Marques et al, 2020). Rajeevan et al (2020) showed that the C-terminus NuMA 2058−2115 fragment is sufficient to bind DNA in vitro, and the basic amino acids within the region are critical for its interaction with chromatin in cells (Figure 2C). When endogenous NuMA was replaced with mutated versions lacking its DNA-binding ability, cells showed improper chromosome decondensation during mitotic exit and an abnormal nuclear shape (Rajeevan et al, 2020), suggesting that NuMA-DNA interactions are critical for proper regulation of chromosome decondensation during nuclear reformation.…”
Section: Dna-binding Domain In Numa's C-terminal Regionmentioning
confidence: 99%
See 1 more Smart Citation